2019
DOI: 10.2320/matertrans.l-m2019827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cerium Addition on Non-basal Slip in Magnesium Single Crystals

Abstract: Cerium, a rare earth element, was alloyed at various ratios with magnesium to create MgCe single crystals which were then subjected to ½ 1100 and ½11 20 tensile tests to clarify effects of cerium on activation of non-basal slips at room temperature. Mg0.016 mol%Ce alloys yielded due to f10 11g twins in ½ 1100 tension tests. Mg0.052 mol%Ce single crystals yielded due to f11 22gh 1 123i second order pyramidal ©c+aª slip (SPCS), similar to pure magnesium single crystals, in ½11 20 tensile tests. Cerium addition d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It has been reported that the critical resolved shear stress (CRSS) for PS [2] and yield stress due to SPCS [3] decreased by lithium addition and CRSS of SPCS [4] decreased by adding cerium. Therefore, by activation of non-basal slips with lithium and cerium addition, improvement of ductility in magnesium alloys would be expected.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the critical resolved shear stress (CRSS) for PS [2] and yield stress due to SPCS [3] decreased by lithium addition and CRSS of SPCS [4] decreased by adding cerium. Therefore, by activation of non-basal slips with lithium and cerium addition, improvement of ductility in magnesium alloys would be expected.…”
Section: Introductionmentioning
confidence: 99%